The reality of the use of the Arabic language in modern media and communication: a study of the causes of decline and ways of advancement. - badis, lehouimel; Hassani, Nour El Houda (El Omda in Linguistics and Discourse Analysis, 2024)
The article aims to provide a general description of the reality of the use of Arabic in the media and communication, as well as solutions that it deems appropriate to advance our Arabic language in modern means of communication and communication. By posing the problem: What is the status of Arabic language in modern means of communication and communication? And what effect it can play in the linguistic component. How can our language be upgraded to meet the requirements of our time? Among the most important results and solutions proposed are: the need to increase national and national awareness of the activation of the role of Arabic in all activities, and the importance of restructuring curricula and programmes in order to serve the Arabic language in practice.